Resilience among bullying victims in coastal areas: examining gender differences - Rober Sandra; Nurfarhanah Nurfarhanah (Journal of Counseling, Education and Society, 2026)
Bullying remains a significant issue among adolescents due to its negative impact on psychological well-being and social adjustment. Resilience is an important protective factor that helps students adapt to and recover from bullying experiences. However, limited research has examined gender differences in resilience among bullying victims living in coastal areas, which are often characterized by unique social and environmental challenges. This study employed a quantitative comparative design involving 237 high school students in coastal areas who had experienced bullying victimization. Participants were selected using purposive sampling. Data were collected using a resilience scale based on emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. Data were analyzed using the Rasch model and Welch test. The findings revealed significant differences in resilience based on gender, with male students demonstrating higher resilience than female students. These findings contribute to the literature by providing empirical evidence on gender-based differences in resilience among bullying victims in coastal communities. The results highlight the importance of considering both individual and contextual factors in understanding resilience and developing support strategies for students who experience bullying.